Antioxidant and Antimicrobial Activities of Extracts From Aerial Parts of Alhagi pseudalhagi - Muhammad, Gulzar; Nadeem Asghar, Muhammad; Ahmad, Mushtaq; Akram Kashmiri, Muhammad; Zia, Iram (Asian Journal of Chemistry, 2010)
In vitro total antioxidant capacity and antimicrobial activity of aqueous and organic extracts from aerial parts of Alhagi pseudalhagi extracts were investigated. Initially, the antioxidant components were extracted in methanol and later subjected to partitioning in solvents of different polarity. Antioxidant and radical scavenging activity of these extracts were evaluated using antioxidant assays such as 2,2'-azinobis(3-ethylbenzothiazoline-6-sulpohonic acid) (ABTS) radical cation scavenging, 2,2-diphenyl-1-picrylhydrazil (DPPH) scavenging, total phenolic contents and total antioxidant activity determination using ferric thiocyanate method. Using ABTSˆ+ decolorization assay A. pseudalhagi extracts showed a wide range of antioxidant activity. Trolox equivalent antioxidant capacity values ranged from 0.888-5.525 mM of trolox equivalents for different fractions of A. pseudalhagi. Using total phenolic contents and total flavonoid contents assays the amount of total phenolics and flavonoids for different fractions of A. pseudalhagi ranged from 10.657-21.759 mg/L of gallic acid equivalents (GAE) and 1.815-10.911 mg/L of quercetin equivalents, respectively. No significant co-relation was found between total phenolic contentss and trolox equivalent antioxidant capacity values. Employing potassium thiocyanate method, inhibition of lipid peroxidation comparable to trolox was exhibited by all the extracts. Antimicrobial activity of these extracts was also found against Bacillus substilis, Escherichia coli, Salmonella typimorium, Pseudomonas aeruginosa and Aspergillus niger. On the basis of the results obtained here A. pseudalhagi may be considered as a rich source of antioxidants and possessing potent antimicrobial activity.